Analysis of reperfusion time trends in patients with ST-elevation myocardial infarction across New York State from 2004 to 2012. (1st April 2017) - Al'Aref, Subhi J.; Wong, S. Chiu; Swaminathan, Rajesh V.; McNair, Patrick; Feldman, Dmitriy N.; Kim, Luke K.; Singh, Harsimran S.; Bergman, Geoffrey; Minutello, Robert M.
Abstract: Background: Registry-driven data have shown a significant decrease in door-to-balloon (DTB) times in patients with ST-elevation myocardial infarction (STEMI) receiving percutaneous coronary intervention (PCI). We sought to determine the trends in reperfusion times (symptom-onset to door (SOTD) and DTB times) in patients presenting with STEMI across New York State. Methods: We retrospectively examined 35, 613 STEMI patients receiving PCI from 2004 to 2012 and compared median SOTD and DTB times across years. Patients with SOTD time > 12 h and DTB time > 3 h were excluded. Results: There was a statistically significant trend towards shorter DTB times (median DTB time of 83 min (IQR 53, 116) in 2004 to a median DTB time of 59 min (IQR 40, 78) in 2012, P  < 0.01 for trend) and SOTD times (median SOTD time of 127 min (IQR 64, 241) in 2004 to a median SOTD time of 116 min (IQR 60, 205) in 2012, P  < 0.01 for trend). In subgroup analysis, demographics and the presence of co-morbid conditions did not influence the trend in reperfusion times. However, women had longer reperfusion times than men in 2012. After adjusting for confounding variables, DTB was a significant predictor of in-hospital mortality (HR = 1.04 (per 10 minutes), P  < 0.01). Conclusions: There was a significant decrease in reperfusion times from 2004 to 2012 in STEMI patients across New York State. This trend was significant regardless of the presence of co-morbid conditions, although a significant gap in reperfusion times persists between men and women.